Editorial - Innovation Management Education in the First Quarter of Twenty-First Century Innovation: Meeting the Challenges and Opportunities - Horwitch, Mel (Senate Hall Academic Publishing, 2007)
The readers of this journal are well aware of the importance of innovation for well-being in the modern economy. Without innovation—the exploitation of technology and knowledge to create improved and new value with regard to markets, firms and other organizations and society at large—we face a gloomy and unappetizing zero-sum future. Maybe that is why so many of us devote significant professional time trying to help others learn how to do a better job creating new things under the sun. Worth repeating, as we also know, innovation is not easy. Successful modern innovation is dynamic and complex, involving an ever-changing and delicate blend of technology, receptive markets and users, effective organization and personal commitment.